THE RELATIONSHIP OF THE NUMBER OF NEUTROFIL LYMPHOCYTE RATIO WITH THE PICTURE OF COLITIS - Br Tarigan, Agita Angela; Xavier Ongko, Nicolas; Edlin, Edlin (Jurnal Impresi Indonesia, 2024)
Colitis is an acute or chronic inflammation of the colon. The gold standard for diagnosis and monitoring of disease activity in colitis patients is endoscopy combined with pathology biopsy. However, endoscopy has disadvantages related to invasiveness, cost, and feasibility of use for long-term follow-up. The neutrophil-lymphocyte ratio is a simple biomarker that can serve as a useful biomarker for diagnosing and predicting mucosal inflammation in colitis. This study aims to determine whether there is an influence between the number of neutrophil-lymphocyte ratios and the appearance of colitis. This research is a cross-sectional observational analytical research. In this study, 44 medical record data were used. A total of 44 colitis medical record data for the 2022-2023 period were collected. The largest age group is 61-70 years with 11 people (25%), based on the gender group the largest is male with 30 people (68.2%), and based on histopathology the largest is 25 (56.8%) patients. who suffers from chronic colitis. However, in the study, there was no relationship between the neutrophil-lymphocyte ratio and the appearance of colitis, P = 0.22 (P value> 0.05) and the Prevalence Ratio 95% CI 1,436 (0,832-2,476). Based on the results of this study, the majority of patients are male, based on the patient's age, the majority is between 61-70 years, and based on the histopathology picture, the majority is chronic colitis. However, in the study, there was no relationship between the neutrophil-lymphocyte ratio and the appearance of colitis, P = 0.22 (P value > 0.05), and the 95% Prevalence Ratio was 1,436 (0,832-2,476).